Pengembangan Bahan Ajar Berbasis Kontekstual pada Pembelajaran Tematik untuk Meningkatkan Kemampuan Berpikir Kritis - Meilinda Anjarsari; Rochmiyati Rochmiyati; I Wayan Distrik (Bulletin of Counseling and Psychotherapy, 2022)
This reseach and development aims contextual-based teaching materials that are valid, practical, and effective in improving students' critical thinking skills fifth grade elementary school students. Type of research and development used refers to the theory of R&D Borg and Gall. The population of this research is schools located in the Ahmad Yani Cluster, Sekampung District, East Lampung Regency. The sample of this research is the fifth-grade students of SDN 2 Giriklopomulyo. Data collection techniques in the form of documentation, questionnaires, and tests. Data analysis used qualitative analysis with descriptive percentage for expert and practitioner validation, and quantitative analysis with Rasch program for validity and reliability and SPSS program to test effectiveness. The results of this study indicate that the contextual-based teaching materials that were developed are valid and practical to use based on the results of expert validation and the results of the questionnaire responses of educators and students. The results of the N-Gain test and paired sample t-test obtained a significant value <0.05. These results show that contextual-based teaching materials are effective in improving the critical thinking skills of fifth grade elementary school students.